Transplantasi Terumbu Karang Berbasis Citizen: Strategi Pendampingan Generasi Muda Desa Karae untuk Konservasi Pesisir: Citizen-Based Coral Reef Transplantation: A Youth Mentorship Strategy for Coastal Conservation in Karae Village - Alim Setiawan; Budiyanti Budiyanti; Sekar Alim Padar; Arwin Arwin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Karae Village, Siompu District, possesses coral reef ecosystems that are essential to the sustainability of coastal resources; however, these ecosystems are increasingly threatened by destructive fishing practices and low awareness among young people. This community service activity aimed to enhance youth participation and understanding in Karae Village regarding coral reef conservation through a citizen-based coral reef transplantation approach. The program was implemented using a participatory approach comprising preparation, education, transplantation implementation, mentoring, and activity evaluation stages, involving 25 young participants. The results showed that all transplanted coral fragments were in good initial condition and remained stable on the substrate. In addition to producing physical outputs in the form of coral reef transplantation structures, the activity also improved participants’ knowledge, awareness, and environmental attitudes toward the ecological functions of coral reefs and the importance of coastal conservation. The citizen-based approach proved effective in integrating conservation knowledge with practical action and has strong potential to serve as a sustainable community service model for coastal ecosystem management.